Linear discriminant analysis with more variables than observations: a not so naive approach - Silva, A. Pedro Duarte (2011)
A new linear discrimination rule, designed for two-group problems with many correlated variables, is proposed. This proposal tries to incorporate the most important patterns revealed by the empirical correlations while approximating the optimal Bayes rule as the number of variables grows without limit. In order to achieve this goal the new rule relies on covariance matrix estimates derived from Gaussian factor models with small intrinsic dimensionality. Asymptotic results show that, when the model assumed for the covariance matrix estimate is a reasonable approximation to the true data generating process, the expected error rate of the new rule converges to an error close to that of the optimal Bayes rule, even in several cases where the number of variables grows faster than the number of observations. Simulation results suggest that the new rule clearly outperforms both Fisher's and Naive linear discriminant rules in the data conditions it was designed for.